Investigation on Microblasting Applied to CrN Coatings. (30th March 2016) - Montesano, Lorenzo; Pola, Annalisa; Gelfi, Marcello; La Vecchia, Giovina Marina
Abstract : A microblasting treatment carried out on CrN coated samples was studied to investigate the induced effect on corrosion and wear resistance. CrN coating was deposited through Cathodic Arc Evaporation technique on quenched and tempered steel. The properties of the coating were studied by hardness measurements, scratch, potentiodynamic, and pin-on-disk tests. The results show that microblasting reduces the corrosion resistance while improving the wear behavior.